FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI ANAK BALITA DI DESA TELUK RUMBIA KECAMATAN SINGKIL KABUPATEN ACEH SINGKIL TAHUN 2012 - Muhammad Ihsan; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Malnutrition is a disorder caused by a deficiency or imbalance of nutrients needed for growth and development. Basic Health Research reported that prevalence rate of children with overweight is 4,2%, good nutrition status is 72,1%, mild nutrition status is 16,6%, and severe nutrition status is 7,1%. The purpose of this study is to determine factors related to nutritional status children under five years old in Teluk Rumbia Village, Singkil Sub-District, Aceh Singkil in 2012. This study is a descriptive study with Cross Sectional Design.  The population is all children under five year old specifically ranged from 12 to 59 months in Teluk Rumbia Village totaling 106 samples. The sampling technique is total sampling totaling 106 children under five. The results of study found that prevalence rate of children under five who good nutrition status is 69.8%, mild nutrition status is 27.4%, and severe nutrition status is 2.8%. Further, the majority of children under five is  male (60.4%), age range from 12 to 35 months (66%), no exclusive breastfeeding (67, 9 %), complete immunization (59,4%), low education of mother (92,5%), lack of knowledge (55,7%), unemployed mother (90,6%), number of child more than 2 children (68,9%), having a history of infection disease (55,7%), having no a history of upper respiratory infection (73.6%) and getting good health service (80,2%). Results of bivariate analysis consists of six variables that have a significant correlation with malnutrition among children under five are exclusive breastfeeding (p=0,005, RP=3,306), immunization (p=0,010, RP=2,141), knowledge of mother (p=0,027, RP=2,063), history of infection disease (p=0,027, RP=2,036), history of upper respiratory infection(p=0,029, RP=1,906), and history of diarrhea (p=0,000, RP=2,973). Thus, it is recommended to the relevant institutions to increase health education programs in order to increase knowledge and awareness of mothers who have children under five about health of their children. Key Word: nutritional status, children under five years old, cross sectional.